Quality of chilli (Capsicum annuum L.) variety Co-3 as influenced by levels and sources of phosphorus and levels of nitrogen - Murugan, M (Journal of Spices and Aromatic Crops, 2001)
Nitrogen and phosphorus application increased the ascorbic acid content and capsaicin content in green, ripe and dry chilli. Sources of phosphorus did not have any significant effect on the ascorbic acid content. The maximum ascorbic acid content was recorded in green fruit which decreased gradually with maturity of fruit, recording the lowest value in dry pod, while capsaicin content was lowest in green fruit and maximum in dry pod.